Pengetahuan Bantuan Hidup Dasar dengan Pelaksanaan pada Perawat - Santi, Maya; Paturohman, Asep; Ria, Roma Tao Toba Muara; Hartoyo, Bona Dwiramaiaya; Lelasari, Margarita Dewi (Journal of Telenursing (JOTING), 2024)
This study aims to determine the relationship between knowledge and the implementation of essential life support in inpatient nurses at the Hospital. The quantitative research method was cross-sectional, with a sample of 68 nurses in the inpatient room of the hospital. The results of this study obtained a p-Value of 0.032 = <0.05, with a positive correlation direction, which means that the higher the nurse's knowledge, the better the implementation of essential life support. The conclusion is that there is an influence between knowledge of critical life support and implementation in nurses. Keywords: Basic Life Support, Implementation, Knowledge